Early career researchers and their authorship and peer review beliefs and practices: An international study. Issue 2 (27th December 2019) - Jamali, Hamid R.; Nicholas, David; Watkinson, Anthony; Abrizah, Abdullah; Rodríguez‐Bravo, Blanca; Boukacem‐Zeghmouri, Cherifa; Xu, Jie; Polezhaeva, Tatiana; Herman, Eti; Świgon, Marzena
Abstract : This article reports on the findings of an international online survey of early career researchers (ECRs) with regard to their authorship and peer review, attitudes, and practices, which sought to discover how the new wave of researchers were utilizing these key aspects of the scholarly communications system. A questionnaire was developed on the back of a 3‐year longitudinal, qualitative study and was distributed through publisher lists, social media networks, university networks, and specialist ECR membership organizations. Identical English, Polish, Russian, Chinese, Spanish, and French versions of the questionnaire were used. Results from 1, 600 respondents demonstrated that 82.7% had co‐authored a paper, and most had performed a variety of authorship tasks. Almost half the respondents reported being subject to various authorship policies, although a quarter said they were not aware of any such policies. Almost all Chinese ECRs reported being subject to authorship policies, but only a third of UK ECRs reported the same. Three‐quarters of ECRs had experience in responding to peer review, and half had been peer reviewers. Half the respondents had a good experience of review and viewed it as a valuable way to improve their authorship skills. However, there was some criticism of some shortcoming such as lengthy peer review and superficial or uninformed comments by reviewers. Double‐blind review was the preferred methodology, and there were few suggestions for how to improve the review process.